Sarcoidosis: proteomics and new perspectives for improving personalized medicine. (3rd October 2018) - Landi, Claudia; Carleo, Alfonso; Cillis, Giuseppe; Rottoli, Paola
ABSTRACT: Introduction : Through synergistic approaches integrating biomedical data from omics sciences to the clinical practice, precision medicine aims at more accurate identification of risk factors, characterization of endotypes, patient stratification, establishment of individualized therapy, and prediction of outcomes. Areas covered : This review evaluates the potential role of different omics approaches for the development and application of precision medicine to sarcoidosis patients. This systemic and heterogeneous inflammatory disease is of unknown etiology, affects people of any age, and requires genotypic and phenotypic characterization. The latter can be achieved through the integration of genomic (i.e. information about genes and their mutations potentially involved in sarcoidosis), transcriptomic (reflecting the dynamic state of a cell and measuring the transcribed genes over time), and proteomic data (i.e. proteins in bronchoalveolar lavage, lung tissues, lung cells, serum and immunity system). Expert commentary : Genomic studies have revealed numerous aspects of sarcoidosis; however, for precision medicine, it is necessary to implement genomics with other omic approaches. The improving reliability of omics data, their storage, and their bioinformatics processing represents the next step to recapitulate in silico biological systems, with the final aim to simulate potential molecular pathways involved in the pathology and useful for clinical purposes.